Diverse Excretion Pathways of Benzyl Glucosinolate in Humans after Consumption of Nasturtium (Tropaeolum majus L.)—A Pilot Study. Issue 20 (28th August 2018) - Kühn, Carla; Kupke, Franziska; Baldermann, Susanne; Klopsch, Rebecca; Lamy, Evelyn; Hornemann, Silke; Pfeiffer, Andreas F. H.; Schreiner, Monika; Hanschen, Franziska S.; Rohn, Sascha
Abstract : Scope: Different metabolic and excretion pathways of the benzyl glucosinolate breakdown products benzyl isothiocyanate and benzyl cyanide are investigated to obtain information about their multiple fate after ingestion. Detailed focus is on the so far underestimated transformation/excretion pathways—protein conjugation and exhalation. Methods and results: Metabolites, protein conjugates, and non‐conjugated isothiocyanates are determined in plasma, urine, and breath of seven volunteers after consuming freeze‐dried nasturtium or bread enriched with nasturtium. Samples are collected up to 48 h at selected time points. The metabolites of the mercapturic acid pathway are detectable in plasma up to 24 h after consumption. Additionally, mercapturic acid is the main metabolite in urine, but non‐conjugated benzyl isothiocyanate is detectable as well. Protein conjugates show high amounts in plasma even 48 h after consumption. In breath, benzyl isothiocyanate and benzyl cyanide are detectable up to 48 h after consumption. Conclusion: Isothiocyanates are not only metabolized via the mercapturic acid pathway, but also form protein conjugates in blood and are exhaled. To balance intake and excretion, it is necessary to investigate all potential metabolites and excretion routes. This has important implications for the understanding of physiological and pharmacological effects of isothiocyanate‐containing products. Abstract : In order to balance intake, metabolism, and excretion of glucosinolates and their breakdown products in humans, several pathways have to be investigated. Therefore, blood, urine, and exhaled air are collected from volunteers in this study after consuming different nasturtium‐containing food matrices. Metabolites of the mercapturic acid pathway, protein conjugates, as well as non‐conjugated breakdown products are investigated at selected time points up to 48 h after consumption.